Homogeneous precipitation at solid/solution interface as a novel chemical route for synthesis of nanoparticles: application to Cd(II) and Pb(II) sulfides. Issue 1 (1st January 2018) - Shoukry, Adel F.; Shuaib, Nadia M.; Ajadi, Abdulhakeem A.
ABSTRACT: Nanoparticles of CdS and PbS were prepared by a novel method in which a sparingly soluble salt of the metal is brought into contact with the preparation solution mixture, without mixing, to introduce Cd 2+ or Pb 2+ ion into the medium at infinitesimal doses. The aqueous solution mixture contained n -heptane; thioacetamide, as sulphide ion precursor; cetyltrimethylammonium bromide (CTAB), as capping agent; and n -butanol, as co-surfactant. At the solid/solution interface CTAB-capped nanometal sulphide is formed through a metathesis reaction in extreme dilute medium. UV-visible, FTIR, and X-ray diffraction spectroscopy, as well as transmission electron microscopy were used to characterise the nanoparticles. The results showed that in solution, the diameters of the prepared CdS and PbS are 2.67 and 1.87 nm, respectively. In crystalline form, the corresponding diameters are 3.8–6.6 nm, and 6.88–13.9 nm, respectively. The crystalline structure of CdS is cubic or hexagonal, while that of PbS is face-centred cubic. The FTIR studies proved that CTAB acted as a capping agent of the investigated nanoparticles.